Sports injury and illness incidence in the Rio de Janeiro 2016 Olympic Summer Games: A prospective study of 11274 athletes from 207 countries - Soligard, T.; Steffen, K.; Palmer, D.; Alonso, J. M.; Bahr, R.; Lopes, A. D.; Dvorak, J.; Grant, M. E.; Meeuwisse, W.; Mountjoy, M.; Pena Costa, L. O.; Salmina, N.; et al. (British Journal of Sports Medicine, 2017)
Objective: To describe the pattern of injuries and illnesses sustained during the Games of the XXXI Olympiad, hosted by Rio de Janeiro from 5 to 21 August 2016.